A novel adaptive state of charge estimation method of full life cycling lithium‐ion batteries based on the multiple parameter optimization. Issue 5 (20th May 2019) - Cao, Wen; Wang, Shun‐Li; Fernandez, Carlos; Zou, Chuan‐Yun; Yu, Chun‐Mei; Li, Xiao‐Xia
Abstract: The state of charge (SoC) estimation is the safety management basis of the packing lithium‐ion batteries (LIB), and there is no effective solution yet. An improved splice equivalent modeling method is proposed to describe its working characteristics by using the state‐space description, in which the optimization strategy of the circuit structure is studied by using the aspects of equivalent mode, analog calculation, and component distribution adjustment, revealing the mathematical expression mechanism of different structural characteristics. A novel particle adaptive unscented Kalman filtering algorithm is introduced for the iterative calculation to explore the working state characterization mechanism of the packing LIB, in which the incorporate multiple information is considered and applied. The adaptive regulation is obtained by exploring the feature extraction and optimal representation, according to which the accurate SoC estimation model is constructed. The state of balance evaluation theory is explored, and the multiparameter correction strategy is carried out along with the experimental working characteristic analysis under complex conditions, according to which the optimization method is obtained for the SoC estimation model structure. When the remaining energy varies from 10% to 100%, the tracking voltage error is <0.035 V and the SoC estimation accuracy is 98.56%. The adaptive working state estimation is realized accurately, which lays a key breakthrough foundation for the safety management of the LIB packs. Abstract : A new idea is proposed to construct the splice equivalent model, in which the optimization strategy of the circuit structure is studied by using the aspects of equivalent mode, analog calculation, and component distribution adjustment and reveal the mathematical expression mechanism of different structural characteristics. A novel particle adaptive unscented Kalman filtering iterative calculation algorithm is designed to explore the state characterization mechanism of the packing lithium‐ion batteries, in which the incorporate multiple featured information.